Mối quan hệ giữa kế hoạch thuế và lựa chọn chính sách kế toán: Vai trò điều tiết của nhà đầu tư nước ngoài tại thị trường Việt Nam - Nguyễn Văn, Hương; Lê Thị Thanh, Huệ; Nguyễn Thị Kim, Anh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
This study analyzes the relationship between tax planning and accounting policy choices, providing empirical evidence from non-financial firms listed on the Ho Chi Minh City Stock Exchange from 2020 to 2024. The regression analysis results from 1,267 firm-year observations confirm that tax planning has a strong and statistically significant impact on accounting policy choices. Notably, the study finds that this relationship is not constant but is significantly moderated by the level of foreign ownership. Foreign ownership plays a restraining role in the positive relationship between tax planning and accounting policy choices. This may be due to transparency pressures and the need for compliance with international standards imposed by foreign shareholders. Furthermore, firm-specific characteristics such as size and financial leverage are also found to have a significant influence on accounting policy choices.
Keywords: Tax planning; Accounting policy choice; Foreign ownership; Size; Leverage ratio